Design And Build Virtual Reality Photography Web-Based To Support Tourism - Indri Tri Julianto (Journal of Electrical, Electronic, Information, and Communication Technology, 2021)
Tourism is the activity of visiting tourist objects for recreational and leisure purposes. Along with developments in the world of technology and information, there is a technology that can be used to promote a tourist attraction called Virtual Reality. Virtual Reality is a technology designed to allow users to interact with a computer-simulated environment. The problem is that there are still very few travel websites that provide this feature. Virtual Reality technology in the world of photography is known as Virtual Reality Photography. Virtual Reality Photography can produce images in 360o, so people can see the image as a whole and as if they were in place when the photographer was taking pictures. The purpose of this research is to design and build a website that provides information for tourists who want to visit tourist objects. The development method used is the Multimedia Development Life Cycle. The output of his research is a Virtual Reality Photography website that provides information in the form of 360o images equipped with location maps and static images. Augmented Reality technology can be applied on this website as a form of information presented as well as Virtual Reality technology.Keywords— Information, Multimedia, Tourism, Virtual Reality, Web.